STRATEGI BELAJAR, WUJUD BAHASA, DAN FUNGSI ILOKUSI DALAM KEMAHIRAN BERBICARA BAHASA ARAB - Imam Asrori (Jurnal Ilmu Pendidikan, 2016)
Learning Strategies, Language Forms, and Illocutionary Functions in Arabic Speaking Skills The objectives of this study were to reveal the kinds and application of language learning strategies in developing Arabic speaking skills, the language forms produced as represented by the complexity of sentences and the oral fluency, and the illocutionary functions in the Arabic speech. The data were analyzed using the theories on learning strategies, psycholinguistics, and speech act. The findings obtained were as follows. The kinds of language learning strategies used included the memory, cognitive compensation, metacognitive, affective, and social strategies, as well as two other strategies. The types of sentences produced were simple sentences, sentences without clauses, compound sentences, and compound complex sentences. The Arabic speech was less fluent moving to fluent, with a number of speech impediments, that is, pauses, repetitions, correction, non functional words, slips of the tongue, and stutter. Three illocutionary functions were found in the Arabic speech, namely, representative, directive and expressive functions.